Cold responses and hormonal echoes: a comprehensive view of Raynaud’s vascular dysfunction - Manal Fardoun (16328847) (2025)
Raynaud’s phenomenon is a peripheral vascular disorder characterized by exaggerated vasoconstrictive response to certain stimuli, most typically cold exposure and emotional stress. Interestingly, Raynaud’s phenomenon incidence is significantly higher in premenopausal females compared to age-matched males, highlighting a role of the female hormone, estrogen, in Raynaud’s phenomenon pathogenesis. Indeed, estrogen plays a fundamental role in potentiating the expression and function of α2C adrenoceptor (α2C-AR), the sole mediator of local cooling-induced vasoconstriction. Due to the mosaic nature of Raynaud’s phenomenon involving vascular, hormonal, and neuronal factors, as well as due to the lack of an appropriate animal model, the pathogenesis of Raynaud’s phenomenon is not fully elucidated. Consequently, despite various therapeutic approaches aimed at mitigating symptoms of Raynaud’s phenomenon, a definitive treatment for Raynaud’s phenomenon is quite challenging and remains an unmet need. Therefore, a better understanding of the underlying pathophysiologic mechanisms of Raynaud’s phenomenon is crucial to better delineate pharmacotherapeutic targets to help fight this elusive disease. In this paper, we dissect the molecular and cellular mechanisms underlying Raynaud’s phenomenon and its risk factors, and we shed more light on the role of estrogen. We also explore traditional and current therapeutic approaches, including pharmacologic and non-pharmacologic treatments. In addition, we discuss how the advancement in molecular research offered promising avenues of Raynaud’s phenomenon treatment, namely drug repurposing and molecular targeting. Nonetheless, enhanced awareness, precaution, and good patient compliance are critically important in preventing the progression of Raynaud’s phenomenon and reducing its severity. Other Information Published in: Inflammopharmacology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10787-025-01792-0